Redox imbalance is related to HIV and pregnancy. - Vanessa Martinez Manfio; Karen Ingrid Tasca; Jessica Leite Garcia; Janaina de Oliveira Góis; Camila Renata Correa; Lenice do Rosário de Souza (PLoS ONE)
Redox imbalance may compromise the homeostasis of physiological processes indispensable to gestational development in HIV-infected women. The present study aims to evaluate markers of the redox system in the development of pregnancy of these women. HIV-positive pregnant women, HIV-negative pregnant women and non-pregnant were studied. Redox markers superoxide dismutase (SOD), catalase (CAT), protein carbonylation and malondialdehyde (MDA) were assessed at first or second trimester, third trimester and postpartum from pregnant and from non-pregnant women. According to the longitudinal analysis model, CAT activity was increased in the postpartum in HIV-positive women and before delivery in HIV-negative women. Increased carbonylation was observed in the pre-delivery period of HIV-negative pregnant women and MDA concentrations were higher in HIV-positive pregnant women compared to those non-infected by HIV at all times. According to the factorial model, higher SOD and CAT activities were observed in HIV-positive women in the initial months of pregnancy and in non-pregnant women. Carbonylation at third trimester was more evident in HIV-negative pregnant women. MDA levels were higher in HIV-positive pregnant women. Increased oxidative stress may occur in HIV-infected pregnant women. Nevertheless, the HIV virus is not solely responsible for this process; instead, mechanisms inherent to the pregnancy seem to play a role in this imbalance.